Polymer electrolyte blends of mono-carboxylic acid-modified epoxidized natural rubber and poly(ethyleneoxide) - Karim, Wan Nurhidayah A.; Ng, Jin Guan; Chan, Chin Han; Yahya, Rosiyah; Gan, Seng Neon (American Chemical Society, 2018)
Natural rubber with 50% of isoprene units epoxidized (ENR50) was treated with excess of mono-carboxylic acids to completely ring open the epoxide groups. The reaction was carried out by heating ENR50 dissolved in toluene with each of acetic and benzoic acid separately at 105 °C. The ring-opening reaction has produced hydroxyl-OH and ester-O-COR groups, leading to an increase in Tg. The products were characterized by Fourier transform infrared spectroscopy, nuclear magnetic resonance spectroscopy, thermal gravimetric analysis, and differential scanning calorimetry. By the solution casting method, each of the modified ENR50s was blended with poly(ethylene oxide) (PEO) in various ratios in toluene, and 2% lithium perchlorate (LiCIO4) was added as the dopant. Results show that the modified ENR and PEO formed incompatible blends. The PEO spherulite growth rate in the blends increased with PEO content. The electrical conductivity was found to increase with the weight fraction of PEO in the blend. At the ratio of 25/75, the acetic acid-modified ENR50/ PEO blend exhibits a conductivity value of 3.1 3 10 × 8 S cm × 1. The benzoic acid-modified ENR50/PEO achieved conductivity of 5.8310 × 7 S cm × 1 at the ratio of 30/70. These blends form conducting polymer electrolytes with potential application in batteries.